Hemodynamic response pattern of spatial cueing is different for social and symbolic cues - Lockhofen, Denise Elfriede Liesa; Gruppe, Harald; Ruprecht, Christoph; Gallhofer, Bernd; Sammer, Gebhard; Justus Liebig University Giessen (My University, 2014)
Directional social gaze and symbolic arrow cues both serve as spatial cues, causing seemingly reflexive shifts of an observer s attention. However, the underlying neural substrates remain a point at issue. The present study specifically addressed the differences in the activation patterns associated with non-predictive gaze and arrow cues, placing special emphasis on brain regions known to be involved in the processing of social information [superior temporal sulcus (STS), fusiform gyrus (FFG)]. Additionally, the functional connectivity of these brain regions with other areas involved in gaze processing and spatial attention was investigated. Results indicate that gaze and arrow cues recruit several brain regions differently, with gaze cues increasing activation in occipito-temporal regions and arrow cues increasing activation in occipito-parietal regions. Specifically, gaze cues in contrast to arrow cues enhanced activation in the FFG and the STS. Functional connectivity analysis revealed that during gaze cueing the STS was more strongly connected to the intraparietal sulcus (IPS) and the frontal eye fields, whereas the FFG was more strongly connected to the IPS and the amygdala.
Keywords: gaze cueing; arrow cueing; functional magnetic resonance imaging; functional connectivity; visual attention; ddc:610